The hundred languages of children : the Reggio Emilia experience in transformation - Edwards, Carolyn P.; Gandini, Lella; Forman, George E., 1942- (Santa Barbrara, Calif. : Praeger, 2012)
"Why does the city of Reggio Emilia in northern Italy feature one of the best public systems of early education in the world? This book documents the comprehensive and innovative approach that utilizes the "hundred languages of children" to support their well-being and foster their intellectual development"--
In collaboration with REGGIO CHILDREN and Innovations in Early Education: the international Reggio exchange.
Includes bibliographical references and index.
BIED
Keywords: Early childhood education -- Italy -- Reggio Emilia; Early childhood education -- United States -- Case studies; Reggio Emilia approach (Early childhood education); EDUCATION / General